2017
DOI: 10.3991/ijim.v11i4.6828
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Mobile Learning Devices in Tertiary Institutions: The Experience of Undergraduates in a Nigerian Private University

Abstract: Abstract-Over the years, technology appears to be making life easier and better. However, in some instances, it appears technology is counterproductive. Mobile learning devices, as the name suggests, have been developed to facilitate learning on the move. The questions are: Are these devices truly facilitating learning? If they are truly facilitating learning, are they facilitating learning positively or negatively? To answer these questions, the survey research design was adopted on a sample of 215 randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Three hundred and seventy seven students were selected to participate in this study. Data were gathered from students across the various colleges in the selected university with the aid of a researcher- made questionnaire based on the works of [2] , [3] , [4] , [5] , [6] , [8] , [9] . The collected data were coded and entered into SPSS version 22 Data analysis was performed; using SPSS-22 Data was analyzed applying inferential statistical tests which involved regression analysis.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Three hundred and seventy seven students were selected to participate in this study. Data were gathered from students across the various colleges in the selected university with the aid of a researcher- made questionnaire based on the works of [2] , [3] , [4] , [5] , [6] , [8] , [9] . The collected data were coded and entered into SPSS version 22 Data analysis was performed; using SPSS-22 Data was analyzed applying inferential statistical tests which involved regression analysis.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The emerging field of learning analytics may be exploited to improve learning outcomes of engineering undergraduates in higher institutions of developing countries towards attaining sustainable education in the region [19] , [20] , [21] . Useful information about the academic performances of undergraduates that studied engineering programs at Covenant University, Nigeria are presented and analyzed in this data article.…”
Section: Datamentioning
confidence: 99%
“…Although, the works of (Odukoya et al, 2017a;Odukoya et al, 2017b) have shown positive impacts of mobile phone and tablets among students, as it could enable students to easily communicate with their parents, friends and relations outside the university but the policy does not prevent students" access to mobile phone; it only provides opportunities to make calls in designated call centres on campus. Apart from that, the policy permits each student to own a tablet which can be used for effective communication through the WhatsApp application.…”
Section: Policies Of the Institution Under Study Fundamental Human Rmentioning
confidence: 99%